2008
DOI: 10.1080/10934520701795434
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of trinitrotoluene in contaminated soils as affected by its initial concentrations and its binding to soil organic matter fractions

Abstract: Trinitrotoluene (TNT), a nitroaromatics, is a major pollutant in explosive contaminated soils. Present study reports the effect of initial concentration of TNT on its degradation kinetics in soils. Soils from two contaminated sites viz. Clausthal and Elsnig, Germany, were mixed with an uncontaminated reference soil to get different initial concentrations (mg/kg) viz Clausthal-1 (54.29), Clausthal-2 (30.86), Clausthal-3 (7.05) Elsnig-1 (879.67), Elsnig-2 (86.43); Elsnig-3 (8.16) and Elsnig-4 (0.99) and were spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…We propose that this is due to the high levels of TNT having an inhibitory effect on any TNT-transforming bacteria within the native soil, and that this time lapse is due to the bacteria adjusting to their heavily TNT-contaminated environment before they could begin to start transforming the TNT. Singh [ 7 ] has shown that high levels of TNT may have a toxic effect on bacteria in soils, and it is likely that this is the case in the native soil, accounting for the lower rate of observed microbial degradation. Other work [ 5 ] has also reported a prolonged TNT half-life due to high levels of TNT in soil and related bacterial inhibition processes.…”
Section: Resultsmentioning
confidence: 99%
“…We propose that this is due to the high levels of TNT having an inhibitory effect on any TNT-transforming bacteria within the native soil, and that this time lapse is due to the bacteria adjusting to their heavily TNT-contaminated environment before they could begin to start transforming the TNT. Singh [ 7 ] has shown that high levels of TNT may have a toxic effect on bacteria in soils, and it is likely that this is the case in the native soil, accounting for the lower rate of observed microbial degradation. Other work [ 5 ] has also reported a prolonged TNT half-life due to high levels of TNT in soil and related bacterial inhibition processes.…”
Section: Resultsmentioning
confidence: 99%
“…As many explosives are toxic and can have adverse environmental effects, a large body of research has been directed towards the detection and remediation of such explosives residues in soil. Explosives bioremediation research to date can broadly be classified into two groups, the first being research involving historical field-samples of explosives-contaminated soil [2][3][4][6][7][8][9][10][11], and the second being research starting with blank, explosives-free soil, with explosives spiked into the soil to assess their degradation and transformation [5,.…”
Section: Introductionmentioning
confidence: 99%